The last days of the Midnight Ramblers - Tomlinson, Sarah, 1976- (Flatiron Books, 2024)
"Perfect for fans of Daisy Jones & The Six and Almost Famous, a gripping debut about the complicated legacy of a legendary rock band and the ghostwriter telling their story. Three Rock & Roll icons. Two explosive tell-all memoirs. One ghostwriter caught in the middle. Mari Hawthorn has just landed the biggest job of her ghostwriting career. Anke Berben, the legendary model and style icon, needs someone for her hotly anticipated memoir. In the 1960s, Anke reveled in headline-grabbing romances with three members of the hugely influential rock band The Midnight Ramblers. The band became as famous for their backstage drama as for their music. Outside of the bandmembers themselves, Anke is the only one who fully understands the tangled relationships, betrayals, and suspicions that has elevated the Ramblers to mythological status. That could not be clearer than in the enduring mystery around the death of Mal, the band's lead singer and Anke's husband, in 1969. In the decades that followed, rumors have swirled about Mal's demise, but Anke and the surviving members of the Ramblers have all kept silent. Until now. As her ghostwriter, Mari must ingratiate herself with Anke, coaxing out the stories she needs to write a memoir worthy of such an important band. Mari is deft at navigating the fatal charms of the rich and famous, having grown up with a narcissistic, alcoholic father. But she soon stumbles upon secrets more explosive than anyone could have imagined. It's now not just about celebrity tell-alls--this is about redemption"--